The role of early human development and multidimensional enhancements in driving space adaptation and Universal Cognition - Ferraz, Marta (Frontiers in Space Technologies, 2025)
This manuscript provides a glimpse into the future of early human development in space environments, underpinned by interdisciplinary research and technological advancements. The implications of early human development in space are analyzed, exploring potential scenarios that could enhance human biology to adapt effectively to these conditions. It is proposed that the initial phases of human development might serve as an optimal period for fostering biological adaptation to space. Such adaptations could pave the way for the emergence of new evolutionary states, establishing the groundwork for a novel human subspecies. The potential for these emerging subspecies to develop the ability to perceive diverse environmental properties hints at a groundbreaking biological era designated here as Universal Cognition.